2018
DOI: 10.1111/cxo.12579
|View full text |Cite
|
Sign up to set email alerts
|

Clinical biomicroscopy and retinoscopy findings of keratoconus in a Middle Eastern population

Abstract: Background: The present work was conducted to investigate the prevalence of clinical biomicroscopy and retinoscopy findings of corneas with keratoconus (KC) at first presentation and their relationship with disease severity. Method: In a prospective cross-sectional study, 371 consecutive KC patients were examined by slitlamp biomicroscopy and retinoscopy at the time of diagnosis. This research evaluates the prevalence of clinical findings such as a corneal protrusion, Vogt's striae, Fleischer's ring, Munson's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…This slit lamp finding also corresponds with stromal haze and hyperreflectivity as observed using confocal microscopy [67]. In severe cases, highly pronounced cones can create a V-shaped deformation of the lower eyelid during downgaze, known as Munson's sign [141,147]. Rizzuti's sign, a bright reflection of the nasal area of the limbus when light is directed to the temporal limbal area, is another sign frequently observed in advanced stages [148].…”
Section: Clinical Featuressupporting
confidence: 62%
See 2 more Smart Citations
“…This slit lamp finding also corresponds with stromal haze and hyperreflectivity as observed using confocal microscopy [67]. In severe cases, highly pronounced cones can create a V-shaped deformation of the lower eyelid during downgaze, known as Munson's sign [141,147]. Rizzuti's sign, a bright reflection of the nasal area of the limbus when light is directed to the temporal limbal area, is another sign frequently observed in advanced stages [148].…”
Section: Clinical Featuressupporting
confidence: 62%
“…The 'scissor reflex' is observed during retinoscopy assessment. Charlouex's oil droplet reflex is also commonly seen in early keratoconus using retroillumination with a dilated pupil, which produces a dark, round shadow in the corneal midperiphery [141]. Fleischer's ring and Vogt's striae can be observed as the disease severity increases (Table 3).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 Naderan et al reported that corneal protrusion, scissoring reflex, corneal thinning, Fleischer's ring, and prominent nerve fibres were the most prevalent findings in the keratoconic corneas (71.7%, 64.2%, 56.6%, 55.5% and 54.7%, respectively). 15 Agrawal et al reported that even though disease severity has a positive relation with anterior segment findings, KC can be diagnosed without AS findings (7%). 4 81% cases had Fleischer ring and Vogt's striae and corneal scarring were more prevalent in severe disease in the study by Agrawal et al 4 CLEK and DUSKS studies reported absence of AS findings in 14% and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes it marked progresion during childhood and puberty that may lead to severe visual loss [3]. Retinal reflection scattering is the earliest findings of keratoconus and corneal reflection on the nasal cornea when a penlight is shone from the temporal side as Rizutti's sign is other early findings [4]. Ocular allergy and itching are play a role in keratoconus etiology [5].…”
Section: Introductionmentioning
confidence: 99%